Pendidikan Islam Transformatif Imam Al-Ghazali: Upaya Mewujudkan Generasi Berakhlak Mulia - Wahju Tri Kusmardiningsih (Postgraduate Study Programme, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
Imam Al-Ghazali, has played a central role in initiating the concept of Islamic education which encourages character transformation as the main foundation. Imam Al-Ghazali views true education in Islam as a fundamental process for changing the nature of individuals. In order to achieve this goal, Imam Al-Ghazali emphasized the need for a holistic educational approach, which not only involves intellectual aspects, but also spiritual and moral. Within the framework of Transformative Islamic Education, a generation with noble morals is the main focus. Imam Al-Ghazali taught that education should not only produce academically intelligent individuals, but also individuals who inherit noble morals, good ethics and high spiritual awareness. This means values ​​such as compassion, honesty, justice and piety must become an integral part of the educational process. Efforts to create a generation with noble morals in Transformative Islamic Education include a deep understanding of religion, deep self-reflection, and consistent practice of worship. prioritizes the concept of lifelong learning, where individuals continuously develop their knowledge and character throughout their lives. Therefore, Transformative Islamic Education which is inspired by the thoughts of Imam Al-Ghazali aims to create a generation with noble morals by integrating intellectual, spiritual and moral aspects in education. This approach views education as a tool to form individuals who are not only academically intelligent, but also have noble morals and deep spiritual awareness. The result is a positive contribution to society and the world more broadly.